Smoking is a risk factor for recurrence of intestinal stricture after endoscopic dilation in Crohn's disease. Issue 4 (3rd December 2012) - Gustavsson, A.; Magnuson, A.; Blomberg, B.; Andersson, M.; Halfvarson, J.; Tysk, C.
Summary: Background: Endoscopic balloon dilation is an efficacious and safe alternative to surgery as treatment of short intestinal strictures in Crohn's disease (CD). Factors predicting outcome of the procedure are not well described. Aim: To evaluate whether smoking at diagnosis, treatment with azathioprine, or other clinical variables may affect clinical outcome after endoscopic dilation. The endpoint was requirement of a new intervention such as dilation or surgery with intestinal resection or strictureplasty. Methods: Retrospective study of 83 patients with CD who underwent endoscopic balloon dilation of an intestinal stricture between 1987 and 2009. Results: After index dilation 55/83 patients underwent a new intervention. Among current smokers, 31/32 (97%) underwent another intervention compared to 18/33 (55%) among never smokers (adjusted HR: 2.50, 95% CI: 1.14–5.50, P = 0.022). After 5 years, cumulative probability of new intervention was 0.81 in smokers compared to 0.52 in never smokers; difference 0.29 (95% CI: 0.07–0.52, P = 0.01). In 16 patients, therapy with azathioprine was initiated before or shortly after the index dilation; 7/16 underwent a new intervention compared to 48/67 of those without azathioprine (HR: 0.46, 95% CI: 0.21–1.03, P = 0.06). After adjustment for other variables, the association was even weaker (HR: 0.80, 95% CI: 0.29–2.18, P = 0.668). Sex, age at diagnosis, age at first dilation, balloon size, location of stricture, and treatment period did not influence outcome. Conclusions: Smoking doubles the risk of recurrent stricture formation requiring a new intervention after index dilation. Maintenance therapy with azathioprine did not influence the subsequent course and need for a new intervention.